Madame Vieux Carré : the French Quarter in the Twentieth Century. - Ellis, Scott S. (University Press of Mississippi, 2009)
Celebrated in media and myth, New Orleans's French Quarter (Vieux Carr) was the original settlement of what became the city of New Orleans. In Madame Vieux Carr, Scott S. Ellis presents the social and political history of this famous district as it evolved from 1900 through the beginning of the twenty-first century. From the immigrants of the 1910s, to the preservationists of the 1930s, to the nightclub workers and owners of the 1950s and the urban revivalists of the 1990s, Madame Vieux Carr examines the many different people who have called the Quarter home, who have defined its character.